1987
DOI: 10.1177/000348948709600422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycerol on Inner Ear Fluid Electrolytes and Osmolalities in Guinea Pigs

Abstract: Endolymph of the scala media (SM) and perilymph of the scala vestibuli (SV) and scala tympani (ST) were collected from the basal turn of anesthetized guinea pigs before and after intravenous administration of glycerol (3 g/kg). Sound-evoked responses were recorded during the test periods. Blood, CSF, and perilymph of the ST were also collected continuously after the injection. The osmolalities and chloride concentrations of the collected samples were determined. In another experiment, the continuous changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, in the clinical diagnosis of Ménière’s disease, the sugar alcohol glycerol is administered orally or intravenously to increase the serum and perilymph osmolarity and thereby osmotically drain the hydropic endolymphatic fluid space and temporarily improve audiometric hearing thresholds (in the early disease state when endolymphatic hydrops remains reversible) [ 54 ]. This finding implies that endolymphatic hydrops in Ménière’s disease is a consequence of osmotic imbalances that can be temporally compensated by osmotically forced (induction of perilymphatic hyperosmolarity) water outflow from the endolymph across the boundaries of the cochlear duct epithelium, as demonstrated in vivo [ 17 , 18 , 49 , 65 , 82 ]. In line with (i) and (ii), the serum (and perilymph) osmolarity [ 9 ] and the AQP5 membrane abundance in OSCs (present study) are both controlled by the autonomic system.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in the clinical diagnosis of Ménière’s disease, the sugar alcohol glycerol is administered orally or intravenously to increase the serum and perilymph osmolarity and thereby osmotically drain the hydropic endolymphatic fluid space and temporarily improve audiometric hearing thresholds (in the early disease state when endolymphatic hydrops remains reversible) [ 54 ]. This finding implies that endolymphatic hydrops in Ménière’s disease is a consequence of osmotic imbalances that can be temporally compensated by osmotically forced (induction of perilymphatic hyperosmolarity) water outflow from the endolymph across the boundaries of the cochlear duct epithelium, as demonstrated in vivo [ 17 , 18 , 49 , 65 , 82 ]. In line with (i) and (ii), the serum (and perilymph) osmolarity [ 9 ] and the AQP5 membrane abundance in OSCs (present study) are both controlled by the autonomic system.…”
Section: Discussionmentioning
confidence: 94%
“…We hypothesize that glycerol alters the fluid composition of the vestibular apparatus and impairs its ability to activate vestibular mediated reflexes. Animal studies examining the effect of glycerol on the vestibular apparatus have demonstrated a change in the electrolyte concentrations within the perilymph and endolymph in both the guinea pig (18,36) and the rat (24). These changes in perilymph and endolymph are rapid, have their maximal effect at 60 to 90 min, and last for several hours (18,24,36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that glycerol can reduce intraocular pressure by decreasing cerebrospinal fluid volume (3), decreasing intracranial pressure (4), and causing fluid shifts within the inner ear in humans (24,35). Glycerol can also modify the electrolyte concentration of both the perilymph and endolymph within the inner ear (18,24,36). Currently, no studies have investigated the direct effect of fluid shifts of the inner ear on the VSR in humans.…”
mentioning
confidence: 99%